Upaya Meningkatkan Pemahaman Bahaya Bullying Melalui Bimbingan Klasikal pada Siswa - Ade Novera Prahardika (Universitas Ahmad Dahlan, 2014)
This study aims to investigate the dangers of bullying through increased understanding of classroom guidance on eighth grade students of SMP Muhammadiyah 3 Yogyakarta Academic Year 2012/2013. The results showed that after being given a classical guidance services, understanding the dangers that are in the category of very high that the number of frequency of Â 23 by 71, 875%. In the category of very high already reached more than half the number of students. In the high category with a number of frequencies 6, 18, 75%, moderate category frequency number 3 for 9, 375%, the low category number 0 of 0%, the category of very low with the number of frequencies 0 of 0%. Thus, it can be concluded that the classical guidance is effective and innovative strategies to improve the understanding of eighth grade students of SMP Muhammadiyah 3 Yogyakarta on understanding the dangers of bullying. The results of this study can be used as reference material for the teacher guidance and counseling to improve understanding of the dangers of bullying on students through classical counseling services in schools.